P224 The sexual health of the homeless – an outreach sexual health screening project. (18th May 2015) - Stockwell, Sarah; Dean, Gillian; Cox, Travis; Tweed, Marc; Poole, Jane; Hume, Georgina; Nicolson, Steven; Hutchinson, Laura
Abstract : Background/introduction: Homeless people are at increased risk of STIs, and may struggle to attend conventional services. To improve sexual health access and knowledge for this group, THT launched a weekly outreach testing project for asymptomatic clients in June 2014 at the local homeless service. HIV point of care tests (POCT) and self-taken STI screens (SHS) were offered. Hepatitis B/C POCTs were introduced more recently. Aim(s)/objectives: To assess the value of the outreach service and describe project outcomes. Methods: User demographics and testing outcomes were collected at each attendance and reviewed at 6 months. Results: From June to December 2014, 129 clients presented. 83% were white British, 92% were male. The mean age was 36 (range 19–65 years). 84% identified as heterosexual, 14% bisexual and 2% homosexual. Only 26% had previously tested for HIV. Of the asymptomatic service users, 45% had a HIV test (all negative) and 23% had a self-taken SHS. Two cases were positive; one urethral chlamydia, one rectal gonorrhoea. Eighteen referrals were made to the local SH clinic for symptomatic screens, blood-borne virus (BBV) testing, vaccination and contraception. Since introducing hepatitis POCTs 2 weeks ago, 4 clients have tested and 2 were positive for hepatitis C. Discussion/conclusion: Prior to project launch, this client group had significant anxiety regarding HIV and BBV. Having the ability to access a full SH screen in familiar surroundings was welcomed. A significant number of infections have been identified demonstrating the importance of the outreach project, and the need for strong links with mainstream services.